Effectiveness of implementation of Diversion at Prosecution Level (Case Study at Judiciary State of Banggai) - Astutik, Inti (Universitas Tadulako, 2019)
ABSTRACTÂ The Main Problem of this research is the effectiviness of implementation of diversion at the level of procesution in the case of the child. This is an empricialjuridicial research or direct research conducted in the field supported by laws and books related to how to uncover the laws that live in society. Main data of thois research is primary taken trhough one real picture of practice in the procesution of a child case. The problem background of this research is criminak acts number commited by children. Furthermore, an effort to prevent and to overcome them needs to be contuducted through implementing, criminal justice system of children. The result of this research revealed that handled procesutioncase in state procesutor of Banggai has been found that the implementation of diversion is difficult to achieve in terms of deliberation because it is very had to bring together all parties. Therefore, all child cases handled by state procesutor of BanggaiprocesutedÂ in the Banggai District Court because diversionÂ at the level of procesution has not been effective. Constraints faced in theprocesution of child deals with the law that the parties are reluctan to attend in the process of diversion even though they get picked up. The victim,s family wants the criminal offender to be processed in court as well as inadequate facilities and infrastructures, as is the result of interviews with the public prosecutor.Keywords :Effectivennes of Implementation of Diversion at Prossucition Level